Existing Islamic Fatwaâ€™s and Guidelines Pertaining to the Usage of Subject and Style in Visual Art: the Literature Discussion and Research Gap Identification - Ramli, Ishak; Mokhtar, Mumtaz; Haimi Md. Zain, Dâ€™zul; Rahimi Osman, Muhamad; Noorman Masrek, Mohamad; Abdul Aziz Ab Gani, Muhamad; Mohd Zamri, Zarlina (International Journal of Engineering and Technology, 2018)
There have been various research studies in Islamic art and Muslim art; however, the specific research on visual art from the perspective of Islamic law and principles (Shariah) through the usage of subject and style in visual art based on the Malaysian context is limited. Thus, this paper aims to review the existing Islamic fatwas and guidelines pertaining to the usage of subject and style in visual art and to identify the gap in visual art from the Islamic view-point research. The result shows that there are several deficiencies which could be discovered by researchers: 1) visual art should be seen from the various types of subject (â€œthe livingâ€ such as humans and animals; the â€œnon-livingsâ€ which are nature and man-made; and hybrid images) and style (representational, stylization and abstraction); 2) based on the discussion of visual art ambiance, the new Islamic viewpoint should be obtained from the Malaysian Islamic Shariahâ€™s experts and later, discussed. Recommendation is given by using the qualitative approach for conducting further researches in this field of study.Â Â